1990
DOI: 10.1007/bf03005615
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalaemia during massive blood transfusion in paediatric craniofacial surgery

Abstract: Children undergoing major craniofacial surgery (MCFS) oftenHyperkalaemia is a recognized complication of massive blood transfusion with whole blood. Both the quantity of blood transfused and the rate of blood transfusion have been identified as risk factors.L-4Since the introduction of blood component therapy in the 1970's, all whole blood donations are separated into specific cellular and plasma components for storage. Therefore blood loss during surgery requires transfusion of each blood component. Massive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 23 publications
1
44
1
Order By: Relevance
“…Although we did not routinely measure the potassium concentration from our stored or fresh blood products, the exogenous potassium load from a unit of PRBC is thought to increase as shelf life increases; because of the need to store continuously massive quantities of PRBC and challenges in shipping from US-based sources to locations within the theater of operations in Iraq, the average shelf life of a unit of PRBC is between 30 and 35 d at our hospital. Brown et al (16) showed that the amount of potassium that is contained in the small plasma component of a stored unit of PRBC seems to plateau at approximately 20 d and averages Ͼ3.7 mmol at this time, representing a clinically significant source of exogenous potassium if multiple units are given. However, as these authors pointed out, there is wide variability in the plasma potassium concentration of stored PRBC, independent of shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not routinely measure the potassium concentration from our stored or fresh blood products, the exogenous potassium load from a unit of PRBC is thought to increase as shelf life increases; because of the need to store continuously massive quantities of PRBC and challenges in shipping from US-based sources to locations within the theater of operations in Iraq, the average shelf life of a unit of PRBC is between 30 and 35 d at our hospital. Brown et al (16) showed that the amount of potassium that is contained in the small plasma component of a stored unit of PRBC seems to plateau at approximately 20 d and averages Ͼ3.7 mmol at this time, representing a clinically significant source of exogenous potassium if multiple units are given. However, as these authors pointed out, there is wide variability in the plasma potassium concentration of stored PRBC, independent of shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the potassium load of transfused blood is redistributed within 30 min [11] but this is dependent upon several variables such as circulating blood volume and cardiac output [12], site of administration and acid base status.…”
Section: Discussionmentioning
confidence: 99%
“…In case reports hyperkalemia-induced situations needing reanimation are described [41,42]. Retrospective evaluations of massively transfused collectives represent transient hyperkalemias, which regulate until the end of the period of transfusion [43][44][45]. Other investigators could not prove the expected increase of K + [46][47][48], and further study groups warn of a hypokalemia during massive transfusion [49][50].…”
Section: Hyperkalemiamentioning
confidence: 99%